Environmental soil physics - Hillel, Daniel (Academic Press, 1998)
The book describes the soil as a central link in the continous chain that constitutes the terrestrial environment: a medium that generates and subtains life, while serving to recycle waste products. It reveals how the functioning of the soil can be affected by human action. It desscribes the dynamic cycles of energy, water, solids, solutes, mineral, gases, and living organisms in the soil. It is self-contained and self-explanatory, with numerous illustrations ans sample problems, up-to-date references, and relevance to real-world conditions